Evaluation of the risk factors for recurrence and the development of epilepsy in patients with febrile seizure - Civan, Ahmet Burak; Ekici, Arzu; Havali, Cengiz; Kiliç, Nevin; Bostanci, Muharrem (Arquivos de Neuro-Psiquiatria, 2022)
Background Although febrile seizure (FS) is generally considered benign and self-limiting, there are differences regarding the risk factors, the prognosis, and the development of epilepsy.Objective To examine the clinical and sociodemographic characteristics of patients diagnosed with FS, and to determine the risks of recurrence and the development of epilepsy.Methods Between 2015 and 2019, we performed a retrospective evaluation of 300 patients with FS followed for at least 24 months.Results The first episode of FS was simple in 72.7% of the patients and complex in 27.3%, and it recurred in 40%. Age under 12 months in the first FS, complex FS, and neurodevelopmental delay were found to statistically increase the risk of recurrence (p < 0.05). A total of 7% of the patients developed epilepsy, and this rate was found to be higher in patients with neurodevelopmental delay and long-term use of antiepileptic drugs (p < 0.001). The development of epilepsy was also observed in 77.8% of the patients with abnormal electroencephalogram (EEG). Epilepsy developed more frequently in those with abnormal EEG (p<0.001).Conclusions Neurodevelopmental delay was an important risk factor for FS recurrence and the development of epilepsy. Abnormality in the EEG is an important risk factor for the development of epilepsy. We found that the long-term prophylactic treatment did not cause decreases in the recurrence of FS nor in the development of epilepsy.
Keywords: Fever; Epilepsy; Seizures, Febrile; Recurrence